Dikerogammarus istanbulensis sp. n., a new amphipod species (Amphipoda: Gammaridae) from Turkey with a key for the genus - Özbek, Murat; Özkan, Nurcan (Zootaxa, 2011)
A new amphipod species, Dikerogammarus istanbulensis sp. nov., is described. Specimens were collected from a reservoir, near Silivri district, İ stanbul province, Turkey. The new species is similar to Dikerogammarus bispinosus Martynov, 1925 except for the presence of setae on inner surface of basal segment of pereopod 7 in both sexes and absence of long setae on the ventral side of second peduncle segment of antenna 1. In addition, epimeral plate 2 has many setae along the ventral margin in both sexes. A detailed morphological description and illustrations of the new species are given. Differences between the new species and related species are discussed. An identification key for the genus Dikerogammarus is presented.